Association between polymorphism in the promoter region of lncRNA GAS5 and the risk of colorectal cancer - Wang, Yajie; Wu, Shenshen; Yang, Xi; Li, Xiaobo; Chen, Rui (Bioscience reports, 2019)
The growth arrest special 5 (GAS5), as a research hotspot of long noncoding RNAs (lncRNAs), has been reported to be associated with colorectal cancer (CRC). However, the association between polymorphisms in GAS5 and the risk of CRC was not clear. In the present study, a case–control study in 1078 CRC patients and 1175 matched healthy controls was performed to evaluate the association between the potential functional genetic variants in GAS5 and the risk of CRC. PCR-TaqMan, qPCR, dual-luciferase assay, electrophoretic mobility shift assay (EMSA), flow cytometry, migration and invasion assays were performed to evaluate the function of polymorphism. Results showed that subjects carrying the rs55829688 CT/TT genotypes had a significantly higher risk of CRC when compared with the CC genotype. Further qPCR assay confirmed that the CRC tissues with rs55829688 CT/TT genotypes had a higher GAS5 mRNA expression level. The dual-luciferase assay, qPCR and EMSA assay revealed that rs55829688 T>C polymorphism could decrease the expression level of GAS5 by impacting the binding ability of the transcription factor Yin Yang-1 (YY1) to the GAS5 promoter region. The expression of apoptosis-related proteins were detected by Western blot. Further, flow cytometry, migration, and invasion experiments showed that GAS5 repressed apoptosis and increased invasion and migration capability of CRC cells. Taken together, our findings provided evidence that the rs55829688 variant in the GAS5 promoter was associated with the risk of CRC and decreased expression of GAS5 by affecting the binding affinity of the transcription factors YY1 to GAS5.